2020
DOI: 10.1177/0305735619899137
|View full text |Cite
|
Sign up to set email alerts
|

Giving voice to jazz singers’ experiences of flow in improvisation

Abstract: Jazz instrumentalists’ experiences of improvisation have informed psychological research on a range of topics including flow in improvisation, yet there is scant evidence of jazz singers’ improvising experiences. Using interpretative phenomenological analysis (IPA), this study investigated the experiences of three professional Australian jazz singers who improvise extensively in their performance practice: How do these singers experience improvisation? IPA of semi-structured interviews with the singers resulte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…In 2023, Wrigley and colleagues found that flow experience in musical practice did not fluctuate substantially for different age groups, genders, or used music instrument families [102]. In accordance with these findings, the state of flow has been observed with improvising jazz musicians [29] and piano players [21]. Loepthien et al discovered that flow and subjective well-being are related for individuals with a highly flexible self-concept and evidence between flow, previous musical practice, and music experience [55].…”
Section: Related Work 21 Mental Effects Of Music Collaborationmentioning
confidence: 84%
See 1 more Smart Citation
“…In 2023, Wrigley and colleagues found that flow experience in musical practice did not fluctuate substantially for different age groups, genders, or used music instrument families [102]. In accordance with these findings, the state of flow has been observed with improvising jazz musicians [29] and piano players [21]. Loepthien et al discovered that flow and subjective well-being are related for individuals with a highly flexible self-concept and evidence between flow, previous musical practice, and music experience [55].…”
Section: Related Work 21 Mental Effects Of Music Collaborationmentioning
confidence: 84%
“…Furthermore, musicians that participate in music-making activities can enter the state of flow [21,29], which was originally introduced by Csikszentmihalyi et al in 1975 [15]. In the musical context, this state can be described as a joyful state of complete absorption in the act of music-making [16].…”
Section: Related Work 21 Mental Effects Of Music Collaborationmentioning
confidence: 99%
“…In contrast, contemporary common-practice classical western music training places less emphasis on improvisation. Improvisation is an integral part of jazz, which has always been a male-dominated field (Caudwell, 2010;Forbes, 2020;Wehr, 2016).…”
Section: Connection Between Improvisation and Flow By Gender And Genrementioning
confidence: 99%
“…May be pursued for its own sake absent meaning, positive emotions or relationships; includes external markers of success and mastery as well as the perception of accomplishment (Seligman 2011, 18-20) (Lamont et al 2018;Lee, Davidson and Krause 2016). The PERMA element of engagement has been explored in many studies on music and flow (Tan and Sin 2019), including in education (Custodero 2002) and jazz singing (Forbes 2020). These studies demonstrate that the PERMA model is an illuminative lens through which to explore the complex processes of music practice and participation (see further Croom 2015).…”
Section: Accomplishment Subjective and Objectivementioning
confidence: 99%